Women's, children's, and adolescents' health in humanitarian and other crises. (14th September 2015) - Zeid, Sarah; Gilmore, Kate; Khosla, Rajat; Papowitz, Heather; Engel, Danielle; Dakkak, Henia; Rahab, Njoki; Sharma, Anita; Fair, Mollie
Abstract : The worst rates of preventable mortality and morbidity among women, adolescents, and children occur in humanitarian and other crises. Sarah Zeid and colleagues discuss the specific attention that is needed for women, adolescents, and children in crises and fragile settings